2007
DOI: 10.1002/ab.20236
|View full text |Cite
|
Sign up to set email alerts
|

Does war beget child aggression? Military violence, gender, age and aggressive behavior in two Palestinian samples

Abstract: We examined, first, the relations between children's exposure to military violence and their aggressive behavior and the role of age and gender in that relation in two Palestinian samples. Second, we tested parenting practices as a moderator of the relation between exposure to military violence and aggressive behavior, and third, whether exposure to military violence of different nature (direct victimization versus witnessing) has specific associations with different forms of aggression (reactive, proactive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 45 publications
2
71
1
4
Order By: Relevance
“…Both age groups should be considered in tandem to fully understand the dynamics of violence. Adults and children are more likely to witness traumatic events during humanitarian emergencies, including shelling, gunfire, abduction, torture, destruction of property, death of loved ones and domestic abuse between adults in their own household (Haj-Yahia & Abdo-Kaloti, 2003;Qouta, Punamäki, Miller, & El-Sarraj, 2008). Children who witness conflict or other emergency events are also more likely to show signs of post-traumatic stress and displays of anger and aggressiveness, which may provoke violent reactions from parents, caregivers and peers (Qouta et al, 2008).…”
Section: Relationship Between Humanitarian Emergencies and Violence Amentioning
confidence: 99%
See 2 more Smart Citations
“…Both age groups should be considered in tandem to fully understand the dynamics of violence. Adults and children are more likely to witness traumatic events during humanitarian emergencies, including shelling, gunfire, abduction, torture, destruction of property, death of loved ones and domestic abuse between adults in their own household (Haj-Yahia & Abdo-Kaloti, 2003;Qouta, Punamäki, Miller, & El-Sarraj, 2008). Children who witness conflict or other emergency events are also more likely to show signs of post-traumatic stress and displays of anger and aggressiveness, which may provoke violent reactions from parents, caregivers and peers (Qouta et al, 2008).…”
Section: Relationship Between Humanitarian Emergencies and Violence Amentioning
confidence: 99%
“…Adults and children are more likely to witness traumatic events during humanitarian emergencies, including shelling, gunfire, abduction, torture, destruction of property, death of loved ones and domestic abuse between adults in their own household (Haj-Yahia & Abdo-Kaloti, 2003;Qouta, Punamäki, Miller, & El-Sarraj, 2008). Children who witness conflict or other emergency events are also more likely to show signs of post-traumatic stress and displays of anger and aggressiveness, which may provoke violent reactions from parents, caregivers and peers (Qouta et al, 2008). Adults and older children with post-traumatic stress are prone to perpetrate interpersonal violence themselves (Catani, 2010;Catani, Jacob, Schauer, Kohila, & Neuner, 2008;Catani et al, 2009).…”
Section: Relationship Between Humanitarian Emergencies and Violence Amentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies between generations may reflect specific contextual political and military histories in the participating families. Palestinian children and youth are active in the national struggle for independence, often facing life-endangering military confrontations and sharing adult responsibilities (Qouta et al, 2008). In family therapeutic terms, children’s struggle for national safety can be described as a role reversal (Minuchin, 1974), which might be reflected in the discrepant family dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, supportive, secure, and wise parenting practices can protect children’s mental health, optimal development, and resilience in the life-endangering conditions of war (Betancourt et al, 2011; Cummings et al, 2011; Feldman, Vengrober, Eidelman-Rothman, & Zagoory-Sharon, 2013; Qouta, Punamäki, Miller, & El Sarraj, 2008). A study of Northern Irish children and parents confirmed that secure emotional family relations predicted low levels of psychological distress despite prolonged and severe sectarian and political violence (Cummings et al, 2011).…”
Section: Introductionmentioning
confidence: 99%